A semantic interoperability framework for distributed electronic health record based on fuzzy ontology. (24th April 2020) - Adel, Ebtsam; El-Sappagh, Shaker; Barakat, Sherif; Elmogy, Mohammed
To achieve an efficient healthcare process; the professionals and doctors need to access the complete data about their patients in the suitable time. In the face of that issue; healthcare semantic interoperability is still a huge problem without solving. In this paper, a unified semantic interoperability framework for distributed EHR based on fuzzy ontology is proposed. The lowest layer stores the EHRs heterogeneous data with different models. In the middle layer, the local ontologies are mapped to a global crisp one. The global reference ontology combines and integrates all local ontologies and therefore describes all data. In the user interface layer, any linguistic or semantic queries can be done by dealing with only the global reference fuzzy ontology. We expect that our framework will handle the current EHR semantic interoperability challenges, reduce the cost of the integration process, and get a higher acceptance and accuracy rate than previous studies.